A Novel Type of Non-coding RNA, nc886, Implicated in Tumor Sensing and Suppression - Yong Sun Lee (Genomics & Informatics)
nc886 (=vtRNA2-1, pre-miR-886, or CBL3) is a newly identified non-coding RNA (ncRNA) that represses the activity of protein kinase R (PKR). nc886 is transcribed by RNA polymerase III (Pol III) and is intriguingly the first case of a Pol III gene whose expression is silenced by CpG DNA hypermethylation in several types of cancer. PKR is a sensor protein that recognizes evading viruses and induces apoptosis to eliminate infected cells. Like viral infection, nc886 silencing activates PKR and induces apoptosis. Thus, the significance of the nc886:PKR pathway in cancer is to sense and eliminate pre-malignant cells, which is analogous to PKR's role in cellular innate immunity. Beyond this tumor sensing role, nc886 plays a putative tumor suppressor role as supported by experimental evidence. Collectively, nc886 provides a novel example how epigenetic silencing of a ncRNA contributes to tumorigenesis by controlling the activity of its protein ligand.